2008
DOI: 10.1523/jneurosci.0104-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Interaction between P-Bodies and Transport Ribonucleoprotein Particles in Dendrites of Mature Hippocampal Neurons

Abstract: The dendritic localization of mRNAs and their subsequent translation at stimulated synapses contributes to the experience-dependent remodeling of synapses and thereby to the establishment of long-term memory. Localized mRNAs are transported in a translationally silent manner to distal dendrites in specific ribonucleoprotein particles (RNPs), termed transport RNPs. A recent study suggested that processing bodies (P-bodies), which have recently been identified as sites of RNA degradation and translational contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
132
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(150 citation statements)
references
References 30 publications
17
132
0
1
Order By: Relevance
“…Ultrastructural studies have demonstrated that the P-bodies are condensed fibrillar aggregates as observed in the yeast prion [PSI] 39,40 . In the same way as shown here in the assembly of TDP-43 functional aggregates, assembly of P-bodies is dynamic and, in neurons, is regulated by the neuronal activity 41 . These observations are reminiscent of the non-toxic ~500 kDa oligomers of amyloidogenic molecules found in a new type of pathogenesis pathway 42 .…”
Section: Discussionsupporting
confidence: 53%
“…Ultrastructural studies have demonstrated that the P-bodies are condensed fibrillar aggregates as observed in the yeast prion [PSI] 39,40 . In the same way as shown here in the assembly of TDP-43 functional aggregates, assembly of P-bodies is dynamic and, in neurons, is regulated by the neuronal activity 41 . These observations are reminiscent of the non-toxic ~500 kDa oligomers of amyloidogenic molecules found in a new type of pathogenesis pathway 42 .…”
Section: Discussionsupporting
confidence: 53%
“…[11][12][13] Third, mRNP granules exhibit dynamic interactions with one another such as docking, fusion, or apparent maturation from one granule type to the next. Examples include P-body-stress granule docking, fusion 11,14 and apparent maturation, 11,12 P-body-neuronal transport granule docking, 15 P-granule-P-body docking 16 and nuage-P-body fusion, and apparent maturation into sponge bodies. 16,17 The simplest interpretation of such observations is that mRNPs are exchanged between different granules, though this has not been directly demonstrated, 13 and remains an important unresolved issue.…”
Section: Diversity and Similarity Among Different Mrnp Granule Typesmentioning
confidence: 99%
“…This later phenomenon also holds true for specific mRNAs, which exit stress granules and enter translation during the recovery phase. 62,63 Dendritic P-bodies also disassemble upon synaptic activation, 15 which may reflect entry of mRNAs into translation. mRNP granules could also be disassembled via mRNA decay, which is most likely relevant to P-bodies, given their enrichment for the decay machinery, the detection of mRNA decay intermediates within, and a correlative increase in P-body numbers when hard to degrade substrates are present.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations